Desempenho da ventilação natural em áreas densamente ocupadas: análises paramétricas usando CFD - Borges, Jamille Brito (2024)
Urban centers have been experiencing a phenomenon of heat accumulation known as Urban Heat Island (UHI), and one of the factors associated with this issue is the poor performance of natural ventilation in urban areas. Urban configuration plays a crucial role in promoting natural ventilation, as parameters such as the arrangement, spacing, and positioning of buildings relative to wind direction in urban centers affect wind speed and dispersion, leading to increased energy consumption for building cooling and indoor air quality (IAQ) problems. In light of this, the present research aims to analyze the performance of natural ventilation for different generic urban configurations composed of multi-story residential buildings in the context of a humid subtropical climate. The methodology was based on parametric analyses using computational fluid dynamics (CFD), in which 9 different urban blocks with variations in spacing, height, and building positioning were investigated under 2 wind directions (0º and 45º) to identify how these parameters influence wind speed, flow, and pressure coefficients on the façades. The city of Santa Maria (RS) was used as a case study. The results showed significant variation in wind behavior and façade pressures when the proposed variables were altered, even while maintaining the same flow speed conditions. For wind speed data, wind incidence was the most impactful factor, with wind at 45° generating a higher average speed. Regarding pressure coefficients on the central building, the arrangement was the parameter that most influenced the results, with the staggered arrangement being the most effective. The qualitative analysis of velocity contours highlighted the importance of increased setbacks in reducing the occurrence of stagnant air. In terms of verticalization, the increase in building height, combined with progressive spacing, increased wind pressure and speed. The research contributed to understanding wind behavior about the studied parameters and to developing best practices for urban planning that promote natural ventilation in residential urban areas.